PELATIHAN PENGGUNAAN GOOGLE FORM DALAM MENINGKATKAN KOMPETENSI SISWA SMA SWASTA NASIONAL - Sari, Rafika Muspita; Nasution, Atikah Rahmah; Ansi, Rahma Yunita; Masniari, Susi; Karimaliana, Karimaliana (Smart Education, 2025)
Abstract: This community service activity is expected to make students of National Private High School have competence in learning, namely knowledge, skills, and abilities in using technology such as Google Forms to support the learning process. The existence of technology such as Google Forms must be interpreted as an effort to increase effectiveness and efficiency and technology cannot be separated from problems, because technology was born and developed to solve problems faced by humans. In relation to this, educational technology is also seen as a product and process. The method of activity in this community service is carried out based on the approach of the theoretical learning process and practical learning. The application of the practical method by explaining educational material assisted by tools or objects, is demonstrated, with the hope that participants will clearly understand and be able to practice the material that has been explained in the community at some point in the future. Keywords: Competence, Learning, Google Forms